IMPLEMENTATION OF TJSL POLICY FOR ENVIRONMENTAL DEVELOPMENT PROGRAM AT PTPN IV TEA PLANTATION AND FACTORY - Murni Utami; Maryam; Teuku Alfiady; Aiyub; Mauludi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to understand and describe the Implementation of theCorporate Social Responsibility(CSR) Policy for the Community Development Program at PTPN IV Nagori Bah Butong II Tea Plantation and Factory with a focus on the implementation of the Community Development program and the constraints that limit it. The results of the study indicate that the implementation of the CSR policy for the Community Development Program by PTPN IV Kebun and Tea Factory was first implemented in 1996. The implementation of the CSR policy for the Community Development program implemented by PTPN IV Kebun and Tea Factory is considered ineffective. This is because the CSR for the community development program implemented in Nagori Bah Butong II is considered not to have been running consistently and has not had a long-term positive impact. The effectiveness of the implementation of the CSR community development program is hampered by a number of factors in Van Meter and Van Horn's "a model of the policy implementation", including the lack of coordination and communication between PTPN IV and institutions and stakeholders. The large number of proposals received by the company makes PTPN IV implement the most priority programs first while still measuring the resources it has. This study recommends that PTPN IV Tea Plantation and Factory increase resources, both budget and human resources who have expertise in providing training and education, strengthening coordination between sectors, and compliance of implementers with applicable policies.